Study of Pushover Analysis on RC Framed Structure with Underground Structure Considering the Effects of Soil Structure Interaction - Dongol, Nasala; Pradhan, Prachand Man; Manandhar, Suman (Journal of Science and Engineering, 2020)
This study states that the effects of soil structure interaction on the Reinforced Concrete (RC) framed structures is directly influenced by the soil properties of the site. Here, one preexisting structure is taken for the study. The building is a hospital building with two underground basements. Taking into account the actual soil condition of building site, this study provides idea on the soil structure interaction on the structure The properties of springs are calculated from different standard penetration test (SPT) values, Poisson’s ratio and elasticity of soil along the depth of the soil. Entire soil-foundation-structure system is modelled and analyzed using spring approach. Static analysis, response spectrum analysis and pushover analysis (PA) are done in order to find the variations in natural periods, base shears and deflections of the structures by incorporating soil flexibility as compared to structures with conventional fixed base. Pushover analysis is done to evaluate the performance of the structure when modelled in fixed base and spring base system.